Iron isotope fractionation during magmatic-hydrothermal evolution: A case study from the Duolong porphyry Cu-Au deposit, Tibet - Li, J.; Qin, K.; Li, G.; Evans, Noreen; Huang, F.; Zhao, J. (Pergamon, 2018)
Ore-forming fluids ultimately precipitate Fe-bearing sulfides and oxides in hydrothermal ore deposits and the Fe isotopic composition of these minerals can trace magmatic-hydrothermal evolution. Here, we report on the Fe isotopic compositions of a suite of hydrothermal minerals (magnetite, pyrite, and chalcopyrite) and granodiorite porphyry from the giant Duolong porphyry Cu-Au deposit (Bolong and Duobuza section), central Tibet. Most magnetite grains with potassic alteration show only minor d57Fe variation (0.38 ± 0.07‰ to 0.52 ± 0.04‰ in Bolong and 0.68 ± 0.02‰ to 0.77 ± 0.08‰ in Duobuza), consistent with the equilibrium fluid d57Fe (~-0.3‰ and ~-0.1‰ respectively) at ~550–480 °C. The equilibrium fluids have lighter Fe isotope signatures than the Duolong granodiorite porphyry (d57Fe = 0.03 ± 0.06‰ to 0.07 ± 0.02‰), corroborating the hypothesis that exsolved fluids should have a lighter Fe isotopic composition relative to parental magmas. Chalcopyrite from the mineralized Bolong and Duobuza porphyries have relatively consistent d57Fe values of -0.60 ± 0.07‰ to -0.42 ± 0.07‰ and -0.40 ± 0.08‰ to -0.30 ± 0.05‰ respectively, with equilibrium fluids at ~450–350 °C having lighter d57Fe values of ~-0.7‰ and ~-0.6‰. The trend of decreasing d57Fe values in evolved fluids likely reflects Rayleigh fractionation of magnetite enriched in heavy Fe isotopes. This supposition is supported by the lighter d57Fe value (0.25 ± 0.07‰) recorded in magnetite that equilibrated with a lighter d57Fe fluid (~-0.5‰) at ~470 °C. Compared to chalcopyrite, pyrite from the Bolong and Duobuza sections have heavier d57Fe values of 0.35 ± 0.06‰ to 0.71 ± 0.06‰ and 0.53 ± 0.06‰ to 0.71 ± 0.07‰ respectively. The pyrite values correlate variably with the Fe isotopic composition of ore-forming fluids (d57Fe = -0.6‰ to -0.7‰), likely due to variations in the degree of Fe isotope exchange between pyrite and fluid. Moreover, combined with previously published Fe isotopic compositions of hydrothermal minerals from oxidized and reduced ore deposits, the results show that chalcopyrite in oxidized hydrothermal deposits always has a lighter Fe isotopic composition than chalcopyrite from reduced hydrothermal deposits. This is likely controlled by melt composition and precipitation of magnetite/pyrrhotite-bearing mineral assemblages. Therefore, the Fe isotopic composition of chalcopyrite could be a useful diagnostic tool for distinguishing oxidized from reduced fluids in hydrothermal systems.